Caregiver Inclusion in IDEAL Discharge Teaching: Implications for Transitions From Hospital to Home. Issue 4 (July 2022) - Topham, Emily Wahlquist; Bristol, Alycia; Luther, Brenda; Elmore, Catherine E.; Johnson, Erin; Wallace, Andrea S.
Abstract : Purpose: Despite recognition that unpaid (e.g., family, friends) caregivers (caregivers) play an important role in successful transitions home after hospitalization, limited information is available about whether and how caregiver experiences of discharge align with current strategies for providing high-quality discharge processes, and how these experiences at discharge impact successful transitions home. The purpose of this study was to explore perceptions of caregivers regarding their discharge preparation, focusing particular attention on whether and how they believed discharge preparation impacted postdischarge patient outcomes. Methods: We conducted in-depth, case interviews with four English-speaking caregivers (61–75 years of age). Content analysis was framed by the nature of caregiver involvement proposed by the Agency for Healthcare Research and Quality's (AHRQ's) IDEAL (Include, Discuss, Educate, Assess, Listen) discharge planning strategy. Results: Caregivers reported receiving clear discharge instructions, or basic education, and yet felt only passively included in discharge teaching. Once home, the caregivers reported gaps in their knowledge of how to care for the patient, suggesting key gaps related to knowledge of warning signs and problems. Two of the four caregiver participants attributed a hospital readmission to postdischarge knowledge gaps. Conclusion: The experiences of these caregivers demonstrate how their limited, passive involvement in discharge education may result in suboptimal patient outcomes after hospitalization. Our findings suggest that structured programs aimed at increasing caregiver involvement in discharge, particularly related to assessment of caregiver problem solving, planning, and postdischarge support, are important in efforts seeking to improve care transitions and postdischarge outcomes. Implications for Case Management: This study assesses caregivers' experience with discharge planning and problems they encounter post-discharge, providing case managers with important information regarding the effectiveness of discharge processes. This study of caregiver experiences suggests that the IDEAL discharge planning strategy remains a useful and important framework for case managers to follow when providing discharge services.